158 views
3 votes
Answer question number 29. The question is in the image.

Answer question number 29. The question is in the image.-example-1
User Malik Umar
by
4.8k points

1 Answer

6 votes

Answer:

1

Explanation:

Given the trigonometric function:


\tan\left(-(3\pi)/(4)\right)

First, by the trigonometrical ratios of negative angles:


\begin{gathered} \tan(-\theta)=-\tan(\theta) \\ \implies\tan\left(-(3\pi)/(4)\right)=-\tan\left((3\pi)/(4)\right) \end{gathered}

Now, tan(3π/4)=1, therefore:


\begin{gathered} \tan\left(-(3\pi)/(4)\right)=-(-1) \\ =1 \end{gathered}

The answer is 1.

User Morena
by
6.4k points